TreeNODF: nestedness to phylogenetic, functional and other tree‐based diversity metrics. Issue 6 (17th April 2014) - Melo, Adriano S.; Cianciaruso, Marcus V.; Almeida‐Neto, Mário; Faith, Daniel
Summary Available measures of nestedness consider descriptor variables (e.g. species) as equally associated, ignoring evolutionary or ecological dissimilarities. Here, we introduce treeNODF, a new class of nestedness that takes into account the resemblance of descriptor variables. The method is an extension of the NODF index and can be applied to systems in which the resemblance of descriptor variables is described by a tree‐like object. Computation of treeNODF is similar to NODF, but uses branch lengths instead of the sum of species occurrences. In this way, we can calculate a phyloNODF for metacommunities if a phylogeny is used to account for differences in phylogenetic diversity (PD) and traitNODF if a functional dendrogram constructed from species ecological traits is used to account for the functional diversity (FD) of communities. Similar to NODF, treeNODF can also be used to assess nestedness among species. In this case, envNODF uses a dendrogram describing the resemblance among the environmental conditions of different sites, to test whether rare species occur in a subset of the environmental conditions in the habitats occupied by frequent species. treeNODF is a composite metric that can be additively partitioned into compositional (S.fraction) and tree‐topology (topoNODF = treeNODF – S.fraction) components of the descriptor variables. Tests of treeNODF and its components can be carried out using null models and, if a hypothetical factor is used to order metacommunity data, permutation tests. We show that treeNODF is robust for matrix size and fill, as well as for tree topology. Finally, we illustrate the use of treeNODF by analysing data on Caribbean bats using phyloNODF, traitNODF and envNODF, as well as their composition and tree‐topology components.